The Fruits of El Dorado: The Global Impact of American Precious Metals - Leticia Arroyo Abad; Nuno Palma (European Historical Economics Society (EHES), 2020)
The quest for precious metals and trade routes during the early modern period fundamentally changed the world. What was the global impact of the large deposits of silver and gold which existed in the Americas? In this chapter, we take a global view. We find that in Europe, England and the Netherlands benefited the most. By contrast, the colonizers par excellence, Spain and Portugal, were unable to profit from their colonial expansion. In Latin America, the exploitation of precious mineral resources enabled the geographic expansion of the empire. The direct impact on other parts of the world was negligible; but the long-term political consequences of European presence shaped the world as we know it today.
Keywords: N50; O43; Q33; F54; 330; Denmark; enclosures; land inequality